Front Cover: Aggregation‐Induced Orange‐to‐Red Fluorescence of 2, 5‐Bis(diarylamino)terephthalic Acid Dithioesters (Eur. J. Org. Chem. 36/2016). Issue 36 (December 2016) - Shimizu, Masaki; Fukui, Hiroki; Natakani, Masaki; Sakaguchi, Hiroshi
Abstract : The cover picture shows the luminescent image and crystal packing diagram of a 2, 5‐bis(diarylamino)terephthalic acid dithioester, with colored leaves of Japanese maple trees in the background. The dithioesters are faintly fluorescent in solution, but exhibit efficient emission in the solid state in the orange‐to‐red region. Based on the absorption spectra and theoretical calculations, the optical transition was concluded to involve an intramolecular charge‐transfer from the diarylamino groups to the organosulfanylcarbonyl moieties. Compared with the corresponding 2, 5‐bis(diarylamino)terephthalic acid diesters, the fluorescence spectra in the solid state are significantly redshifted. Details are discussed in the article by M. Shimizu et al. onp. 5950 ff .